Locus of Control and Obesity - Neymotin, Florence; Nemzer, Louis R. (Frontiers in Endocrinology, 2014)
In the developed world, the hazards associated with obesity have largely outstripped the risk of starvation. Obesity remains a difficult public health issue to address, due in large part to the many disciplines involved. A full understanding requires knowledge in the fields of genetics, endocrinology, psychology, sociology, economics, and public policy – among others. In this short review, which serves as an introduction to the Frontiers in Endocrinology research topic, we address one cross-disciplinary relationship: the interaction between the hunger/satiation neural circuitry, an individual’s perceived locus of control, and the risk for obesity. Mammals have evolved a complex system for modulating energy intake. Overlaid on this, in humans, there exists a wide variation in “perceived locus of control” – that is, the extent to which an individual believes to be in charge of the events that affect them. Whether one has primarily an internal or external locus of control itself affects, and is affected by, external and physiological factors and has been correlated with the risk for obesity. Thus, the path from hunger and satiation to an individual’s actual behavior may often be moderated by psychological factors, included among which is locus of control.